OBJECTIVATION OF THE INTROVERT TYPE OF A PERSONALITY IN THE NOVEL"TICKET TO THE STARS" BY V. AKSYONOV - F. Bormusova , Liliya; I. Rakhimov, Dinara; N. Fattakhova, Nailya (Gênero & Direito, 2019)
The current research is executed in the mainstream of psycholinguistics within which the theory of psychological types has been developing in the last decades. The analysis of an introspective psychological type is carried out in the article on the basis of an art discourse viewing which we are guided by the theory of the identity of K.G. Jung. On the material of the story by V.P. Aksyonov "Ticket to the stars" the introspective type of the personality is being investigated for the first time; it is represented by the personage of the graduate student Victor, the elder brother of the main character of the story – of Dimka. In general, being stereotypic, the analyzed character has a number of the individual traits latently pointing to his professional activity. For the description of structure of the core of a psychological type the typified and individual signs are revealed; the share of these signs in the formation of the studied psychological type is defined. The analysis was carried out with the application of the methods of synthesis and generalization.